Examining the Satisfaction Level of Construction Workers Regarding Safety Management in the Kingdom of Saudi Arabia - Suresh, Subashini; Renukappa, Suresh; Alghanmi, Ibrahim; Mushatat , Sabah; Olayinka, Raymond (Penerbit Universiti Sains Malaysia, 2017)
The importance of the construction industry in Saudi Arabia cannot be overemphasised, as it provides the infrastructure required for other sectors of the economy to grow, thus reflecting the level of economic development in the country. However, in Saudi Arabia, the construction industry is among the most hazardous, with a high level of accidents and fatalities. This study examines health and safety practices in the construction industry of Saudi Arabia and identifies opportunities for improvement. It also discusses the safety climate. The study adopted a quantitative approach in which a survey questionnaire was distributed and returned at a 60% response rate. The survey data were analysed using descriptive statistics with SPSS statistical software. The findings show that the Saudi Arabia construction industry has made improvements in health and safety standards; however, there are opportunities for further improvement. There are on-going efforts to maintain reasonable health and safety standards for employees on-site, but conditions off-site, particularly those of migrant employees on fixed-term labour contracts, are difficult. Unpaid wages and lack of welfare facilities contribute to physical and psychological stresses that are linked to impaired on-site performance, lack of motivation, lack of productivity and a lack of interest in adhering to health and safety guidelines. The study concludes that it is possible to improve health and safety in the construction industry through the effective enforcement of existing health and safety laws, enacting legislation regarding off-site health and safety for migrant workers, maintaining a fund for social security, and improving the regulation of commercial and contractual transactions. This study contributes to the knowledge of government policy and decision making in implementing health and safety regulations in the construction industry.